2016
DOI: 10.1016/j.celrep.2016.01.047
|View full text |Cite
|
Sign up to set email alerts
|

An ER-Localized SNARE Protein Is Exported in Specific COPII Vesicles for Autophagosome Biogenesis

Abstract: The de novo formation of autophagosomes for the targeting of cytosolic material to the vacuole/lysosome is upregulated upon starvation. How autophagosomes acquire membranes remains still unclear. Here, we report that, in yeast, the endoplasmic reticulum (ER)-localized Qa/t-SNARE Ufe1 has a role in autophagy. During starvation, Ufe1 is increasingly exported from the ER and targeted to intracellular sites that contain the autophagy markers Atg8 and Atg9. In addition, Ufe1 interacts with non-ER SNARE proteins imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…Previous work has established that ERES and COPII vesicles are required for autophagy in both yeast and mammalian cells (Ge et al, 2014; Graef et al, 2013; Lemus et al, 2016; Suzuki et al, 2013; Tan et al, 2013; Wang et al, 2015). However, because it has been difficult to fully tease apart the function of COPII vesicles on the secretory pathway from their role in autophagy, their contribution to autophagy has been problematic to address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has established that ERES and COPII vesicles are required for autophagy in both yeast and mammalian cells (Ge et al, 2014; Graef et al, 2013; Lemus et al, 2016; Suzuki et al, 2013; Tan et al, 2013; Wang et al, 2015). However, because it has been difficult to fully tease apart the function of COPII vesicles on the secretory pathway from their role in autophagy, their contribution to autophagy has been problematic to address.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosome biogenesis has been linked to COPII vesicles and an ER subdomain called the ER exit sites (ERES) where COPII vesicles are formed (Graef et al, 2013; Suzuki et al, 2013; Tan et al, 2013; Ge et al, 2014; Wang et al, 2015; Lemus et al, 2016). How COPII vesicles, which are faithfully targeted to the Golgi, can be reprogrammed to function on an alternate trafficking pathway during nutrient deprivation remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient deprivation of course also links directly to the field of autophagy. Here, there has been considerable activity in recent years showing key roles for COPII in phagophore initiation (Wang et al 2014), LC3 lipidation (Ge et al 2013, 2014) and autophagosome membrane expansion (Ge et al 2017; Lemus et al 2016). COPII is subject to control by phosphorylation during these events including modification of Sec23 (Gan et al 2017) and Sec24 (Davis et al 2016).…”
Section: Copii and Proteostasis: Autophagy And The Uprmentioning
confidence: 99%
“…We found that the SNARE protein Ufe1, which was previously known for its role in both homotypic ER-ER membrane fusion and heterotypic fusion of retrograde vesicles with the ER membrane, is also required for autophagy. 8 Interestingly, the largely ER-resident Ufe1 was increasingly exported from the ER and routed to the vacuole under conditions that triggered autophagy, i.e., under cellular starvation. Furthermore, Ufe1 transiently co-localized and physically interacted with the autophagy marker proteins Atg8 and Atg9, the latter being an integral membrane protein and prominent component of a pool of cytosolic vesicles that are considered another major source of membranes for autophagosomes.…”
Section: Main Textmentioning
confidence: 99%
“…Support for such a scenario came from our findings that Ufe1 physically interacted with other non-ER SNAREs that had previously been implicated in the formation of autophagosomes. 8 In a subsequent series of experiments we analyzed in more detail the role of Ufe1 in membrane supply to autophagosomes. The key methods used involved thin-section electron microscopy and confocal fluorescence microscopy in combination with 3-dimensional reconstruction.…”
Section: Main Textmentioning
confidence: 99%